The Influence of E-Procurement Implementation, Internal Control Systems, and Whistleblowing Systems on Preventing Procurement Fraud in Government Goods and Services - Suryani, Cindy; Setiany, Erna (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
The increase in corruption cases in Indonesia from year to year has come under the spotlight of various parties where the majority of cases come from the government sector, especially in goods/services procurement. This study aims to analyze the factors that influence the accountability of government performance in fraud prevention. Research data is primary data obtained through questionnaires and analyzed with Partial Least Square (PLS) using the smartPLS program. Research population is procurement actors who are directly involved in the procurement process of goods and services in all work units of the Ministry of Maritime Affairs and Fisheries. Research samples are 100 samples using a purposive sampling method. The results showed that the implementation of e-procurement has a positive effect on preventing fraud in the procurement of government goods and services, and the internal control system has a significant positive effect on preventing fraud in the procurement of government goods and services, and the whistleblowing system has a positive effect on preventing fraud in the procurement of government goods and services. This research is expected to serve as a valuable source of information and a foundation for policy-making, ensuring a more effective procurement process for goods and services within the Ministry of Maritime Affairs and Fisheries